In vitro plant regeneration of Indian jujube (Ziziphus mauritiana Lamk.) cv. Zaytoni via indirect organogenesis - Majid Abdel IBRAHIM; Abbas Mehdi JASIM; Muayed Fadhil ABBAS (Acta Agriculturae Slovenica)
In vitro plant regeneration was achieved in Ziziphus mauritiana Lamk., through de novo formation of meristems in callus obtained from the shoot tip cultured on MS medium supplemented with either IBA (10.0 mg.l-1) or NAA (15.0 mg.l-1) and 5.0 mg.l-1 BA. Organogenic callus was obtained when the primary callus was cultured on MS medium supplemented with BA at 5.0 mg.l-1 .Adventitious shoots were obtained when the organogenic callus was incubated on MS medium supplemented with BA at 1.0 mg.l-1 and NAA at 0.1 mg.l-1. Whole plants were developed when the adventitious shoots were transferred to half strength MS medium supplemented with NAA at 0.2 mg.l-1.